2002
DOI: 10.1193/1.1461375
|View full text |Cite
|
Sign up to set email alerts
|

GPS in Pioneering Dynamic Monitoring of Long-Period Structures

Abstract: rates allows scientifically justified dynamic measurements of relative displacements of long-period structures. The displacement response of a simulated tall building in real time and permanent deployment of GPS units at the roof of a building are described. To the authors ’ best knowledge, this is the first permanent deployment of GPS units (in the world) for continuous dynamic monitoring of a tall building. Data recorded from the building during a windy day is analyzed to determine the structural characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(51 citation statements)
references
References 9 publications
1
50
0
Order By: Relevance
“…For instance, Ashkenazi and Roberts [4] and Brown et al [5] found that the geodetic estimates of the displacement of the deck of the Humber Bridge excited by traffic loads agree with those predicted by FEM analysis. In the second case, Celebi and Sanli [27] found a similarity in the estimates of the natural frequency of a building deduced from GPS recordings and an accelerometer record during an earthquake. Lekidis et al [28] also arrived at a similar conclusion on the basis of the comparison of the spectra of a suspended bridge derived from independent accelerometer, GPS and robotic total station data.…”
Section: Methods To Assess the Accuracy Of Gps Kinematic Techniquesmentioning
confidence: 90%
“…For instance, Ashkenazi and Roberts [4] and Brown et al [5] found that the geodetic estimates of the displacement of the deck of the Humber Bridge excited by traffic loads agree with those predicted by FEM analysis. In the second case, Celebi and Sanli [27] found a similarity in the estimates of the natural frequency of a building deduced from GPS recordings and an accelerometer record during an earthquake. Lekidis et al [28] also arrived at a similar conclusion on the basis of the comparison of the spectra of a suspended bridge derived from independent accelerometer, GPS and robotic total station data.…”
Section: Methods To Assess the Accuracy Of Gps Kinematic Techniquesmentioning
confidence: 90%
“…The recent advances of modern measurement technology such as Global Positioning System (GPS) and robotic total station (georobot) bring new technical measures. The search of literature indicates that GPS can be used to measure the deformations of large construction structures such as cable-stayed bridges, suspension bridges and high-rise buildings [1][2][3][4][5][6][7] . Several simulation trials have shown that GPS is capable of measuring displacement amplitudes above 2 mm and frequencies up to 50 Hz [7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…This has implications which might include building or antenna pole movements due to wind, local vibrations or even sharp temperature changes. However, the dynamic effects of wind are rarely important for building structures of less than 20 stories (Celebi and Sanli 2002)-as is the case in this particular network. Therefore we assume that the GPS antennas (and the reflecting surface) are stationary.…”
Section: Discussionmentioning
confidence: 98%
“…The tallest building in the current GPSnet TM configuration is 16 stories. Therefore detecting pole or building dynamics (if it exists) would require data recorded at better than 1-Hz (Guo and Ge 1997;Ogaja et al 2001;Celebi and Sanli 2002). 2 Fig.…”
Section: Data From the Gpsnet Tmmentioning
confidence: 98%